Converting NCL Documents to Smix and Fixing Their Semantics and Interpretation in the Process - Lima, Guilherme Augusto Ferreira; Azevedo, Roberto Gerson De Albuquerque; Colcher, Sérgio; Haeusler, Edward Hermann (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
In this paper, we present the conversion of NCL to Smix and discuss its main implications. NCL is a declarative language for the specification of interactive multimedia presentations which was adopted by the ITU-T H.761 recommendation for interoperable IPTV services. Smix is a synchronous domain-specific language with a similar purpose, but with a simpler and more precise semantics. By implementing NCL over Smix, we bring to the former the notions of reaction and execution instants, and with them some benefits. From a practical perspective, we fix the semantics of the converted documents, get a leaner NCL player (the Smix interpreter), and simplify further conversions. From a systems-design perspective, the structured conversion of NCL to Smix helps us tame the complexity of mapping the user-oriented constructs of NCL into the machine-oriented primitives that realize them as a multimedia presentation. In the paper, we present NCL and Smix, discuss related work on document conversion, and detail the conversion process and a prototype implementation.